An Early Childhood Sex Education Model: Deconstructing Symbolic Meanings of Sintren Dance based on Gender Perspectives - Asmara, Rangga; Kusumaningrum, Widya Ratna (Asosiasi Pusat Studi Wanita/Gender & Anak Indonesia (ASWGI), 2019)
This study aims to: (1) describe symbols of Sintren dance based on gender perspectives and (2) develop an early childhood sex education model by deconstructing the symbolic meanings of Sintren dance texts based on gender perspectives. This research used two research-designs i.e. semiotic analysis and design based research. Semiotics analysis used is the Derrida’s deconstruction model. The analysed data were from the text of Sintren dance performance of Paguyuban Sintren Sekar Arum Glandang Village, Bantarbolang Sub district, Pemalang Regency. The methods used for gathering the data were observation techniques, documentation studies, and in-depth interviews. The method for analysing the data referred to the Derrida’s deconstruction analysis model, including (1) the interpretation of presence-absence and its difference by unboxing the existing interpretation, (2) the interpretation of trace which refers to the sense of the origin of reality, and (3) reproduction or recreation. Meanwhile, the design-based research procedure was adapted from the Reeves’ model, covered: identifying needs and its potencies from deconstruction process, developing a prototype model, validating the model in the form of expert validation, testing the model, and reflection. The model was constructed to emphasize on the kids’ awareness of their conditions, care, and protection from any sexual harassment. The materials were validated and scored “good” to be used, predominantly it concerns about cognitive, affective, and psychomotor aspects.